The role of probiotics with lactic acid-producing bacteria in modulating the behaviour of rodent model following contusive spinal cord injury: preliminary study - Manickam, Danniya Lakshmi (2023)
The disruption of gut dysbiosis after spinal cord injury (SCI) is a crucial but poorly understood phenomenon that might affect SCI healing. This study addresses the need to examine locomotor recovery after SCI and presents an animal model that may help restore a healthy gut flora and improve SCI therapies. The primary objective is to create a reliable animal model of SCI with gut dysbiosis to test probiotic treatments. With a 10% dropout rate (1 additional rat), this study included 13 rats. Adult female Wistar rats were carefully weighed and randomly allocated to one of four groups: Group 1 (control, n = 3), Group 2 (control with antibiotic intake, n = 4), Group 3 (SCI with antibiotic intake, n = 3), and Group 4 (SCI with antibiotic intake and probiotic therapy, n = 3). A rod was dropped from 25 mm to cause a moderate contusion injury in the T9/T10 thoracic area after a laminectomy. Successful surgery was established by the rats' hindlimb paralysis. Five days before SCI, rats received antibiotic mixtures to produce intestinal dysbiosis. Their drinking water included 2 g/L streptomycin, 0.17 g/L gentamicin, 0.125 mg/L ciprofloxacin, and 1 g/L bacitracin. After surgery, the rats returned to their usual drinking water. Multi-strain probiotic therapy began on the thirteenth day post-SCI and lasted until the eighteenth. Oral forced feeding of 3g of 30 x 109 CFU/kg probiotics in sterile water was performed. Post-injury faeces were tested for gut dysbiosis on days 4, 11, 18, and 25. In addition to faecal sample analysis, the Basso Beattie Bresnahan Locomotor Rating Scale was used to evaluate the rats' behavioural and locomotor recovery on the 4th, 11th, 18th, and 25th dpi for 4 minutes per rat. After six days of probiotic therapy, faecal sample morphology and BBB locomotor assessments showed a mild effect. Overall, this study sheds light on the significant connection between SCI, intestinal dysbiosis, and probiotics. The study found that probiotics may help SCI patients recover locomotion and gut eubiosis. More study is needed to determine the full range of probiotic benefits. This research reveals new ways to improve SCI patients' results and quality of life.